Terapi Musik Untuk Pasien Hipertensi : A Literatur Review - Yulastari, Puti Rania; Betriana, Feni; Kartika, Imelda Rahmayunia (Universitas Fort De Kock Bukittinggi, 2019)
Hypertension and its complications can be minimized by using pharmacological and non- pharmacological therapy. One of the non-pharmacological therapies is musical therapy. This literature review aims to find out how music can affect blood pressure. This literature review follows the method of analyzing PICO (problem, intervention, comparison, outcome) from 20 articles obtained from Google Scholar, Science Direct, and OAJSE from 2001-2018 using the following keywords: 'Musical Therapy', 'Music for Hypertension', and 'Hypertension Therapy'. From 20 articles, the musical therapy showed effective outcome to decrease blood pressure in patients with hypertension, including by using classical music, instrumental music, and moderate frequency music. The result of this literature review recommends the application of musical therapy to decrease blood pressure for patients with hypertension. Keywords: musical therapy, hypertension, blood pressure